FEAR, EXCITEMENT AND HISTORIOGRAPHY - Timmermann López, Freddy (Revista de Historia Social y de las Mentalidades, 2015)
Through the elements of emotion and fear, theoretical relationships to historiography are established, which determines your analytical capabilities. The relevance of building emotional contexts in the study of historiographic objects from a methodology focused on the analysis of discourse in the construction of textual macroforms of fear and its contextual projection. It expands, thus, the understanding of the historical processes by which the individual apprehends and significantly orders his social reality.